2007
DOI: 10.1080/01449290600811594
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating asynchronous discussions in learning communities: the impact of moderation strategies

Abstract: A facilitator or moderator is often responsible for supporting processes and their progress in learning communities. In this article we present an approach for supporting moderators of asynchronous processes in learning communities. This approach follows the socio-technical perspective: it includes a theory-based development of moderator tasks and the technical features designed to support these tasks. Starting with relevant work in this area, we describe our approach to moderator support in the collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Improved student communications skills is often claimed as a potential benefit of asynchronous online discussion (Birch & Volkov, 2007;Kienle & Ritterskamp, 2007;MacKinnon, 2000), but there has been little evidence that this potential benefit has been realised. In this study, the instructor ratings of the achievement of improved student communication skills were significantly higher for the assessed discussion group than for the unassessed discussion group (5.49 versus 4.65, t(41) = 2.056, p=0.046).…”
Section: How Does Having the Student Contributions Assessed Affect Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved student communications skills is often claimed as a potential benefit of asynchronous online discussion (Birch & Volkov, 2007;Kienle & Ritterskamp, 2007;MacKinnon, 2000), but there has been little evidence that this potential benefit has been realised. In this study, the instructor ratings of the achievement of improved student communication skills were significantly higher for the assessed discussion group than for the unassessed discussion group (5.49 versus 4.65, t(41) = 2.056, p=0.046).…”
Section: How Does Having the Student Contributions Assessed Affect Thmentioning
confidence: 99%
“…Zhang, Zhao, Zhou and Nunamaker (2004) argue that within an online environment, we need to 'integrate appropriate pedagogical methods, to enhance system interactivity and personalization, to better engage learners'. Although current studies make significant contributions to the body of knowledge, there is a clear and consistent call for empirical evidence that clearly demonstrates the conclusions often hinted at in many of the studies (Alavi, Marakas & Yoo, 2002;Arbaugh & Hiltz, 2005;Dennen, 2008;Kienle & Ritterskamp, 2007;McKenzie & Murphy, 2000;Schellens & Valcke, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on online social networks indicates that visible feedback, in particular others' comments, increases the motivation to make future contributions [37][38][39][40]. In the field of online learning communities, moderators' comments and summaries have been found to strengthen collaboration [41]. Likewise, in the field of online political debate, it has been found that the presence of an active moderator may increase the quality of the debate [42].…”
Section: The Effect Of Interaction Between User Participants and Devementioning
confidence: 99%
“…Εάν η th International Conference in Open & Distance Learning -November 2013, Athens, Greece -PROCEEDINGS Volume 2 -Section A: theoretical papers, original research and scientific articles 97 κατασκευή της γνώσης είναι μια συμμετοχική διαδικασία, η οποία περιλαμβάνει μερικούς μαθητές, ο κύριος ρόλος του Διαχειριστή είναι να υποστηρίζει και να εμπνέει τις διαδικασίες επικοινωνίας για την απόκτηση της γνώσης, καταλήγοντας σε νέα καθήκοντα για τον ίδιο (Kienle, 2006 . Kienle & Ritterskamp, 2007). Ακόμη, ο ρόλος του διαχειριστή είναι η ενθαρρύνση της αλληλεπίδρασης μεταξύ των μελών της κοινότητας και παράλληλα η δημιουργία υποστηρικτικού και άνετου περιβάλλοντος για τη μεταξύ τους συζήτηση (Winograd, 2003).…”
Section: διαχείριση και λειτουργία διαδικτυακών κοινοτήτων μάθησηςunclassified